Helper-dependent adenoviral vectors for liver-directed gene therapy of primary hyperoxaluria type 1 - Castello, Raffaele (Gene Ther, 2015)
Primary hyperoxaluria type 1 (PH1) is an inborn error of liver metabolism due to deficiency of the peroxisomal enzyme alanine:glyoxylate aminotransferase (AGT) which catalyzes conversion of glyoxylate into glycine. AGT deficiency results in overproduction of oxalate which ultimately leads to end-stage renal disease and death. Organ transplantation as either preemptive liver transplantation or combined liver/kidney transplantation is the only available therapy to prevent disease progression. Gene therapy is an attractive option to provide an alternative treatment for PH1. Towards this goal, we investigated helper-dependent adenoviral (HDAd) vectors for liver-directed gene therapy of PH1. Compared to saline controls, AGT-deficient mice injected with an HDAd encoding the AGT under the control of a liver-specific promoter showed a significant reduction of hyperoxaluria and less increase of urinary oxalate following challenge with Ethylene Glycol (EG), a precursor of glyoxylate. These studies may thus pave the way to clinical application of HDAd for PH1 gene therapy.